Relação entre adesão à massagem perineal e as disfunções do assoalho pélvico: um estudo exploratório - Rafaela França Rocha Neumayr (2013)
Objective: to determine the occurrence of perineal trauma and pelvic floor dysfunctions during pregnancy and after delivery in women that had performed antenatal perineal massage and investigate the relationship between adherence to antenatal perineal massage and pelvic floor dysfunction after childbirth. At last, to determine how women that practiced perineal massage assessed the technique. Methods: longitudinal study with 31 pregnant women who were instructed to perform perineal massage from 34weeks of gestation to delivery. Participants were evaluated on perineal pain (by the verbal numerical rating scale), urinary incontinence (UI) and anal incontinence (AI), defined as a report of at least one episode of incontinence in the last month, according to the definitions of the International Continence Society, and sexual dysfunction (measured by The Female Sexual Function Index - FSFI) at around 34 weeks of gestational age and at 3 to 10 days, 1 and 3 months after delivery. Adherence was documented from participants diaries, and a structured questionnaire was developed to collect information on their opinion about the perineal massage. Perineal trauma data were collected from medical reports and hospital records. To compare the outcomes through the 4 time points, Cochran, Friedman and Kendal statistical tests were used. Chi squared and Kruskall-Wallis tests were used to analyze whether the perineal outcomes were associated with adherence. Level of significance was set at 0.05.Results: 74% of the participants had vaginal delivery, in which 30,4% had intact perineum, 62,5% had firstdegree tear, 37,5% second degree tear and 8,7% had episiotomy. At the third trimester of gestation, 54,8% of the participants had sexual dysfunction, 48,4% reported UI symptoms, 16,1% reported perineal pain and 12,9% had AI. At 3 to 10days after delivery, 69,6% of the participants reported perineal pain, 22,6% reportedIU and 6,5% had AI. One month after delivery, 81,5% had sexual dysfunction; 29,2% had perineal pain, 16.1% reported having IU symptoms and 9,7% had AI. At 3 months after delivery, sexual dysfunction was reported by 34,8%, only 4,3% still reported perineal pain and UI, and none of the participants had AI. Perineal pain significantly increased 3 to 10 days postpartum and decreased until 1 month after delivery (p=0.004); UI significantly decreased until 1 month after delivery (p=0.001). There were no statistical differences on AI throughthe 4 time points. The mean FSFI decreased 1 month and increased 3 months after delivery (p<0.001). The occurrence of normal sexual function was significantly higher in the group of women that performed the perineal massage up to two thirds of the protocol (p=0.013). The mean rate of adherence to perineal massage was 54,5% (SD=29,9). Although 39%of the participants reported that it caused discomfort, all of them would recommend it for other pregnant women. Conclusion: The adherence to the perineal massage influenced the recovery of sexual function. Women from Brazil showed a satisfactory compliance to perineal massage and most of them evaluated it in as positive to outcomes related to their delivery.